Doing More with Less: solutions to Budget Cuts to Municipal Police Departments Based on the Meta-Leadership Concept - Haberfeld, Maria R. (SIAK-Journal, 2010)
This article explores the effects of recession on police departments around the country from the perspective of recruitment, training, supervision and deployment. Strategies for circumventing the cuts and relying on creativity and meta-leadership techniques are introduced and analyzed from the perspective of some possible contributions from the academic body of knowledge to the struggling departments, especially in the areas of budget cuts for police training. The need for creative and forward thinking leadership in police organizations becomes more acute than during the past decades of prosperity and overall decline in crime rates. Historically, when the economy takes a plunge the crime rates go up. We do not need just more officers on the streets - we need them to be prepared for the unforeseen domino effects of high unemployment rates and the quasi anomie state that might follow.